Dimensions of digital literacy based on five models of development / Dimensiones de la alfabetización digital a partir de cinco modelos de desarrollo. Issue 2 (3rd April 2019) - Pérez-Escoda, Ana; García-Ruiz, Rosa; Aguaded, Ignacio
Abstract: Digital literacy has been an emerging and increasing priority in many governments' educational and assessment policies since the first decade of the twenty-first century because it is a priority in citizenship training. The difficulty with understanding and developing it comes from its changing, transversal and flexible nature; for this reason, the fundamental objective of this research is to offer an exhaustive study of the concept by analysing the main models of digital literacy in the international context in order to offer a holistic model that incorporates the contributions from all of these initiatives. The theoretical study presented herein provides an objective, rigorous perspective on the main models of development of digital literacy: the DIGCOMP Project (European Commission), the Krumsvik model (Norway), the TPACK model (USA), the JISC model (UK), the ISTE Standards (USA) and the P21 model (USA). The conclusion offers an innovative proposal of four dimensions that should define digital literacy today, taking into account the five initiatives studied, which could be very worthwhile for researchers, educators and policymakers.